Wellbeing and self-esteem in Icelandic adolescents and the elderly - Karen Sif Óskarsdóttir 1992- (2017)
The aim of this study was to examine differences in self-esteem and wellbeing among adolescents (14 to 16 years) and the elderly (60 to 80 years) in Iceland and to test if self-esteem was a significant predictor of wellbeing in both age groups. To test this comparable questions from two different surveys, Heilsa og líðan íslendinga 2009 from the Directorate of health and Youth in Iceland 2016 from ICSRA, were compared. Response rate for the survey Heilsa og líðan íslendinga 2009 was 77.3%, participants used in the current study were 1834 with the mean age of 70 years. Response rate for Youth in Iceland 2016 from ICSRA was 86% and the participants used in the current study were 2039 with the mean age of 15 years. The main results showed that on average older people had significantly higher levels of wellbeing compared to the adolescents. Older females had significantly higher levels of self-esteem than the adolescents but no differences were found in self-esteem for males. Furthermore, while self-esteem was a significant predictor of wellbeing in both age groups it turned out to be a stronger predictor of wellbeing among the adolescents than the elderly. Markmið rannsóknarinnar var að kanna mun á sjálfsáliti og lífsánægju meðal unglinga (14 til 16 ára) og eldra fólks (60 til 80 ára) á Íslandi og að kanna hvort sjálsfálit væri marktækur áhrifaþáttur lífsánægju fyrir báða aldurshópa. Til að rannsaka þetta voru samanburðarhæfar spurningar teknar úr tveimur spurningakönnunum, Heilsa og líðan íslendinga 2009 frá Landlæknisembættinu og Ungt fólk 2016 frá Rannsóknum og greiningu og bornar saman. Svarhlutfall könnunarinnar Heilsa og líðan íslendinga 2009 var 77.3% og þátttakendur sem notaðir voru í þessari rannsókn voru 1834 með meðalaldurinn 70 ára. Svarhlutfall könnunarinnar Ungt fólk 2016 var 86% og þátttakendur sem notaðir voru í þessari rannsókn voru 2039 með meðalaldurinn 15 ára. Helstu niðurstöður sýndu að eldra fólk hafði að meðaltali meiri lífsánægju en unglingar. Eldri konur höfðu meira sjálfsálit en unglings ...